THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND BREAKFAST HABITS ON WORK FATIGUE IN NURSES IN THE EMERGENCY ROOM OF I.A. MOEIS HOSPITAL SAMARINDA - Muhamad Adji Bayu Saputra; Rieska Indah Mulyani; Diah Retno Wahyunigrum (Sahabat Publikasi, 2023)
Introduction: Occupational fatigue is a common problem among nurses who have a heavy workload. Fatigue can be influenced by various factors, such as nutritional status and breakfast habits. This study aims to determine the relationship between nutritional status and breakfast habits on work fatigue of nurses in the emergency room of RSUD I.A. Moeis Samarinda. Methods: Analytical survey research with cross sectional method, using a sample of all nurses in the ER room totaling 39 people. Data were collected using work fatigue questionnaire, breakfast habits, and anthropometric tools. Data were analyzed using the chi-square test. Results: The results of the analysis of the relationship between nutritional status on work fatigue obtained p-value = 0.989 OR = 0.989, there is no relationship between nutritional status on work fatigue. Breakfast habits on work fatigue obtained p-value = 0.217 OR = 2.286, there is no relationship between breakfast habits on work fatigue. Conclusion: There is no significant relationship between nutritional status and breakfast habits on work fatigue among nurses in the emergency room of RSUD I.A. Moeis Samarinda.